واقع الاتصال التنظيمي في الجمعيات الخيرية التطوعية الشبابية "دراسة حالة للجمعيات الخيرية بولاية الوادي - حسن حدودي; عبد المنعم حرزلي (جامعة الوادي - University of Eloued, 2025)
"هدفت هذه الدراسة إلى معرفة واقع الاتصال التنظيمي في الجمعيات الخيرية الشبابية في ولاية الوادي، وقد تناولت الدراسة الإشكالية الرئيسة التالية: ما واقع الاتصال التنظيمي لدى الجمعيات الخيرية الشبابية التطوعية بولاية الوادي؟ وللبحث عن إجابة لهذا السؤال استخدمت الدراسة المنهج الوصفي والتاريخي لتفسير وتحليل المعطيات، بالاستعانة بأداة المقابلة التي أجريت على عينة من الجمعيات الخيرية النشطة بالولاية، وهي (03) جمعيات خيرية تنشط على المستوى الوطني والدولي أيضا، ثم اعتمدت على التحليل السوسيولوجي والاستدلال النظري في مناقشة المعطيات، وخلصت الدراسة إلى النتائج التالية: - تعتمد الجمعيات الخيرية التطوعية والشبابية في ولاية الوادي على وسائل وقنوات اتصال متنوعة ومختلفة بين تقليدية وحديثة، تسهم كل وسيلة في تجسيد أهدافها على أرض الواقع. - تستخدم الجمعيات الخيرية في ولاية الوادي أسلوب الاتصال النازل، سواء مع أفراد أو مع جماعات. - تهتم الجمعيات الخيرية باستقطاب فئة الشباب ونخبة المجتمع، لتمثيلها في مختلف نشاطاتها داخل الولاية وخارجها، لذلك نجد أن نسبة الشباب كبيرة بين المنخرطين والمتطوعين ذكورا وإناثا. - تحرص الجمعيات الخيرية على تعزيز قيم التعاون بينها وبين جميع فئات المجتمع من أجل تحقيق الرسالة النبيلة من العمل التطوعي والإنساني، وتكريس ثقافة العمل الجمعوي بصفة دائمة حتى ترقى بالمجتمع. - تسعى الجمعيات الخيرية في ولاية الوادي إلى تكاتف المجتمع حولها ودعمها معنويا وماديا، حتى يمكنها الاستمرار في أعمالها ونشاطاتها الإنسانية الخيرية، وتحقق الأهداف التي نشأت من أجلها. - تواجه الجمعيات الخيرية باختلاف نشاطها ومكانها من نقص المورد المالي بالخصوص، فهو تعتبره صمام أمان لبقائها واستمرار عملها، وتناشد الجهات المعنية للالتفاف حولها ودعمها في كل الظروف والأوقات. " The aim of this study is to understand the reality of organizational communication in youth charitable associations in the state of El Oued. The study addressed the main research question: What is the reality of organizational communication in youth charitable associations in the state of El Oued? To answer this question, the study used the descriptive and historical method to interpret and analyze the data, relying on interviews conducted with a sample of active youth charitable associations in the state, which amounted to (03) associations. The study relied on the sociological approach and functional analysis in studying the phenomena and led to the following results: Youth and volunteer charitable associations in the state of El Oued rely on various and different communication channels, both traditional and modern. Each method contributes to embodying their goals on the ground. The charitable associations in El Oued use the downward communication method, whether with individuals or groups. Charitable associations primarily target the youth and elite segments of society to involve them in association activities both inside and outside the state. Therefore, a significant percentage of youth are involved in various volunteer initiatives and events. Charitable associations aim to promote values of cooperation among youth and between all segments of society in order to achieve the noble message of humanitarian and social work and to instill the culture of collective work, which has become almost absent in society. Charitable associations in El Oued strive to keep pace with societal density around them, to fulfill their voluntary and charitable roles and achieve their goals, but still face several difficulties and obstacles. Charitable associations suffer from weak organization and structure and the lack of clear roles among members. This often results in poor performance and limited influence. Therefore, it is necessary to reconsider their internal dynamics and support them to improve their work and achieve their goals.
مذكرة ماستر قسم علوم الاجتماعية تخصص علم اجتماع تنظيم وعمل.
Keywords: استراتيجيات; قنوات الاتصال; الجمعيات الخيرية; الاتصال التنظيمي; Organizational communication; Charitable associations; Communication channels; Strategies